L’incidence des régimes de responsabilité sur l’indemnisation du préjudice en matière médico-hospitalière - Crépeau, Paul-André (Assurances, 1983)
In matters of malpractice liability, there is no doubt that, under the Quebec general theory of obligations, the particular circumstances of each case may well reveal the existence of various legal relations in as much as the liability of each party involved: hospitals, doctors, nurses, technicians and other servants, will constitute either a breach of a contractual obligation or the violation of an extracontractual duty. The purpose of the article is to show, in the light of a recent decision of the Court of Appeal of Quebec in the case of Bernard v. Cloutier, (1982) C.A. 289, that the distinction between the two regimes of liability contractual and extracontractual may have important practical implications.